The health care mess : how we got into it and what it will take to get out - Richmond, Julius B. (Julius Benjamin), 1916-2008; Fein, Rashi (Harvard University Press, 2005)
In this important new book, Julius Richmond and Rashi Fein recount the fraught history of health care in America since the 1960s, showing how the promises of medical advances have not been matched either by financing or by delivery of care. As a new crisis looms, and the existing patchwork of insurance is poised to unravel, American leaders must again take up the question of health care. This book brings the voice of reason and the promise of compromise to that debate.